Impact of a visual indicator on the noise level in an emergency medical dispatch centre - a pilot study - Justin Outrey; Jean-Baptiste Pretalli; Sophie Pujol; Alice Brembilla; Thibaut Desmettre; Christophe Lambert; Jean-Marc Labourey; Frédéric Mauny; Abdo Khoury (BMC Emergency Medicine, 2021)
Abstract Background Noise levels are monitored in call centres. A maximum of 52 to 55 dB(A) is recommended in order to prevent adverse events. We aimed at assessing the noise level and the impact of a visual noise indicator on the ambient noise level in a French Regional Emergency Medical Dispatch Centre (EMDC). Methods We conducted an observational study in the EMDC of the SAMU25 (University Hospital of Besancon). We measured the noise level using a SoundEarII® noise indicator (Dräger Medical SAS, France). The measurement took place in two phases on three consecutive days from 00:00 to 11:59 PM. At baseline, phase 1, the device recorded the average ambient noise for each minute without visual indication. Secondly, phase 2 included a sensor mounted with a light that would turn on green if noise was below 65 dB(A), orange if noise ever exceeded 65 and red if it exceeded 75 dB(A). Results In the presence of the visual noise indicator, the LAeq was significantly lower than in the absence of visual noise indicator (a mean difference of − 4.19 dB; P < 10–3). It was higher than 55 dB(A) in 84.9 and 43.9% of the time in phases 1 and 2, respectively. Conclusions The noise levels were frequently higher than the standards, and sometimes close to recommended limits, requiring preventive measures. The noise indicator had a positive effect on the ambient noise level. This work will allow the implementation of effective prevention solutions and, based on future assessments, could improve operators’ well-being and better care for patient.